การเรียนรู้โดยใช้สถานการณ์จำลองเสมือนจริง: การนำไปใช้ในการจัดการเรียนการสอน - สินธุชัย, สมจิตต์; อุบลวรรณ, กันยารัตน์ (Journal of The Royal Thai Army Nurses, 2017)
การเรียนรู้โดยใช้สถานการณ์จำลองเสมือนจริงเป็นวิธีการเรียนรู้ผ่านประสบการณ์ ผู้เรียนมีส่วนร่วมในกระบวนการเรียนรู้ด้วยตนเองเสมือนอยู่ในสถานการณ์จริง การสรุปผลการเรียนรู้โดยการสะท้อนคิดประสบการณ์จากสถานการณ์จำลองช่วยถ่ายโยงความรู้จากทฤษฎีสู่การปฏิบัติ ผู้เรียนได้ทำความเข้าใจ วิเคราะห์ความคิด ความรู้สึกต่อกิจกรรมที่ได้ปฏิบัติในสถานการณ์ และสรุปหลักการหรือแนวคิดที่จะนำไปประยุกต์ในสถานการณ์ใหม่ ผลลัพธ์การเรียนรู้ดังกล่าวส่งเสริมทักษะการปฏิบัติการพยาบาล การให้เหตุผลทางการพยาบาล การคิดอย่างมีวิจารณญาณ การตัดสินใจทางการพยาบาล และทักษะที่ไม่ใช่การปฏิบัติการพยาบาล ได้แก่ การทำงานเป็นทีม และการสื่อสาร บทความนี้มีวัตถุประสงค์เพื่อใช้เป็นแนวทางสำหรับการจัดการเรียนการสอนโดยใช้สถานการณ์จำลองเสมือนจริงซึ่งสามารถนำไปพัฒนาการจัดการเรียนการสอนเพื่อใหผู้เรียนมความมั่นใจ และมีความสามารถในการปฏิบัติการพยาบาลในสถานการณ์จริงมากขึ้น Fidelity Simulation Based Learning: Implementation to Learning and Teaching Management Fidelity Simulation Based Learning is learning method by experience. Learners have participation in self-learning process as real situations. Learning-result conclusion by experiential reflection from simulation based learning helps connection of knowledge from theory to practice. Learners have understanding, analyzed thinking, feeling to practical activities in the situation, and principle or concept conclusion to apply for new situations. The learning results support nursing practice skills, giving clinical reasons, critical thinking, decision making in nursing, and non-nursing practice skills such as team work, and communication. This article aims to be a guideline for learning and teaching by using simulation based learning. It can bring to develop learning and teaching for the learners to be more confident and able to practice in nursing in the real situation.